2011
DOI: 10.1111/j.1439-0272.2010.01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Male obesity and age in relationship to semen parameters and sperm chromatin integrity

Abstract: Obesity can adversely affect human health, including fertility. While obesity can disturb the hormonal profile of the female organism and is associated with fertility loss, little is known about what effect male obesity has on fertility. The present study analysed sperm samples of 153 donors. The men were selected from couples attending an infertility clinic, who had tried for 12 months or more to achieve pregnancy without success. The age of the men under investigation was recorded, and their body mass index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 31 publications
7
60
2
1
Order By: Relevance
“…Considering that this phenomenon has been extensively studied in humans, these results are in agreement with previous studies that reported a higher DNA fragmentation in aged men (Wyrobek et al, 2006;Rybar et al, 2011). It is known that aging induces apoptosis in the epididymis, which seems to be caused by the fall of testosterone levels and is probably related to an increase of oxidative stress in tissues (Jara et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…Considering that this phenomenon has been extensively studied in humans, these results are in agreement with previous studies that reported a higher DNA fragmentation in aged men (Wyrobek et al, 2006;Rybar et al, 2011). It is known that aging induces apoptosis in the epididymis, which seems to be caused by the fall of testosterone levels and is probably related to an increase of oxidative stress in tissues (Jara et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…Jensen et al [16] reported decreased sperm counts in obese normozoospermic men compared to non-obese fertile subjects. Interestingly, Rybar et al [17] found no significant relationship between mean BMI and standard semen parameters.…”
Section: Introductionmentioning
confidence: 96%
“…The rate of normal sperm morphology did not differ in any of the groups (12). Nevertheless, Rybar et al (13) reported that an elevated BMI did not have an influence on basic semen parameters. Mal-Ali et al (13) concluded that BMI did not have an independent influence on sperm quality parameters based on a multivariable analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, Rybar et al (13) reported that an elevated BMI did not have an influence on basic semen parameters. Mal-Ali et al (13) concluded that BMI did not have an independent influence on sperm quality parameters based on a multivariable analysis. Our finding that BMI has an impact on sperm motility but no impact on sperm morphology is in agreement with Sekhavat et al (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation